2016
DOI: 10.1111/pan.12964
|View full text |Cite
|
Sign up to set email alerts
|

An audit of patient‐controlled analgesia after appendicectomy in children

Abstract: It is feasible that children with uncomplicated appendicitis given intraoperative NSAID can be successfully managed without PCA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…16,18,27 In fact, PCAs are currently still being used for postoperative pain management after appendectomies, though current evidence suggests that the need for a PCA may be declining. 28,29 We felt that utilizing PCAs was crucial for providing a background environment to study the impact of scheduled IVA because each patient would have similar background demands and allow for sensitive detection of a difference created by a nonnarcotic analgesic. The alternative, utilizing as needed medications would introduce too much background noise depending on the threshold of the patient, parent, nurse, and house staff for demanding medications.…”
Section: Discussionmentioning
confidence: 99%
“…16,18,27 In fact, PCAs are currently still being used for postoperative pain management after appendectomies, though current evidence suggests that the need for a PCA may be declining. 28,29 We felt that utilizing PCAs was crucial for providing a background environment to study the impact of scheduled IVA because each patient would have similar background demands and allow for sensitive detection of a difference created by a nonnarcotic analgesic. The alternative, utilizing as needed medications would introduce too much background noise depending on the threshold of the patient, parent, nurse, and house staff for demanding medications.…”
Section: Discussionmentioning
confidence: 99%
“…Below are some suggestions regarding dosing of some of the drugs that may be applicable to the different pain management ladder levels based on the available literature . Table shows dosage suggestions for systemic analgesia, special care must be taken when prescribing opiods in patients with obstructive sleep apnea.…”
Section: Recommendationsmentioning
confidence: 99%
“…6,22 In a retrospective analysis of 649 children undergoing appendectomy by Ousley et al, 94% received intravenous opioids postoperatively. 3 Another U.S.-based study showed 84% of pediatric patients being discharged with a prescription for opioids after laparoscopic appendectomy. 6 The volume of discharged opioid prescriptions is also notable.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there has been a development toward aggressive pain management with liberal opioid adminis-tration in an indiscriminate fashion. 3 This change was due to studies showing a tendency to underestimate postoperative pain leading to inadequate pain management and increased morbidity and mortality. 4,5 However, there is new evidence indicating this more liberal opioid administration might have overshot the target leaving a significant amount of prescribed opioid doses unused.…”
Section: Introductionmentioning
confidence: 99%